Awareness, Perceived Risk and Preventive Practice on Coronavirus Disease (COVID-19) among Cancer Patient in Bir Hospital, Kathmandu - Gautam, Roshani; Paudel, Bishnu Dutta; Shrestha, Rejina; Kalikotay, Bhagawaty (Nepal Medical College Journal, 2021)
People with cancer are at high risk for coronavirus infection because of immunosuppressive nature of disease itself and adverse effect of treatment. Knowledge and adoption of preventive practice is critical to control the outbreak of infectious disease in vulnerable populations. Hence, this study aimed to identify the awareness, perceived risk and preventive practices regarding coronavirus disease among people with cancer. Methods: A descriptive cross-sectional study was conducted among 83 cancer patients in Bir Hospital. Total enumeration sampling technique was used to collect data for two weeks and interview schedule was used. Data was analyzed in SPSS version 16, descriptive and inferential statistics was calculated. Out of 83 participants, mean score of knowledge was 37.33±7.5 and 76% of study participants had adequate awareness (>75% of total score) and the mean practice score was 24.6±2.88. None of the study participants were practicing preventive measures as per guidelines of government. The study found that level of awareness was significantly associated with the age of the participants (p=0.04). However, other socio-demographic factors were not associated with awareness. The study concluded that people with cancer had adequate awareness but had inadequate practices on preventive measures as per the guidelines of the Ministry of Health and Population and WHO, which should be mandatory to contain disease outbreak. Therefore, there is an urgent need to focus on the adoption of preventive behaviors for cancer patients.